Immigration and Training: Problems and Challenges The Case of Chinese immigrants in Finland - Jiang, Meng (My University, 2014)
Immigrant flows are rising all around the world with the process of globalization. For the reasons like economic, social and political factors, immigrants leave their home country and set a new home in host country. At the meantime, multitudinous problems need to be solved by both immigrants and host countries. Immigration training is useful for most immigrants in their new home country. Intercultural immigration training is different from traditional migration training. Its goal is to educate them on language, literacy, local working skill, and basic living information, and help them to overcome culture difference. As a result, the two main questions in this research are to find the problems and challenges of immigrants in new intercultural environment, and to figure out the demanding immigration training for different cultural groups. The Chinese immigration in Finland is chosen as a case study to analysis the theoretical basis. What is more, the method of intercultural management research is used to analysis the cultural confliction. Additionally, both feedback of interviews and reliable multi-documents are mainly sources of case study evidences. Finland is not the ideal immigration place for most Chinese immigrants in the beginning. Seeking higher salaries, better education for children, better welfare system, and social factor (marriage) are main reasons for Chinese immigrate to Finland. With the process of setting a new life in foreign country, they have to deal with the problems like incommunicability, joblessness and resourcelessness. Besides, Finland is a typical low-context cultural country, while China is a perfect model of high-context cultural. The cultural difference between Finland and China covers education for children, eating habits and customs for sure. There are at least 6 different types of immigration training in Finland. While the related authorities of immigration training include but are not limited to Kela, Opetushallitus and Maahanmuuttovirasto. As a result, it is confusing for immigrants in the beginning, they are not sure the place and authority of the training. Most of them even do not know what the first step of immigration training is. Moreover, for those who have used to study in the past or currently take part in the immigrant training program, they point out the ideal immigration training is not only language or working skills in the long run, but also the living guidance and cultural information for a short time. Moreover, psychological counseling also plays a significant role in the adaptation of intercultural immigrants.
Keywords: Immigrant; immigration training; cross-cultural management; intercultural communication; public management; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|